PENGARUH MOTIF MENONTON VLOG “MAUDY AYUNDA’S BOOKLIST” TERHADAP KEPUASAN MAHASISWA MEMPEROLEH INFORMASI - Juniarti, Gita (Virtu: Jurnal Kajian Komunikasi, Budaya dan Islam, 2023)
Technological developments have led to video bloggers, also known as vlogs. Vlogs are not only used to convey information about entertainment, but vlogs also function as educational forums. One of the vlogs with hundreds of thousands of subscribers and millions of viewers is Maudy Ayunda's Booklist vlog. The vlog tells about interesting things from non-fiction books read by Indonesian actress Maudy Ayunda. This study uses the uses and gratifications theory. Based on this theory, this study analyzes gratifications obtained as student motives for watching vlogs towards gratifications sought, namely student satisfaction after watching the vlog. The purpose of this study is not only to analyze the influence of student motives on satisfaction in watching vlogs but also to analyze the magnitude of the influence of these motives on viewing satisfaction. The findings from this study indicate that students' motives for watching vlogs influence viewing satisfaction. This study uses a quantitative approach and analyzes using simple regression. Questionnaires were distributed to 400 students in 10 faculties at Gorontalo State University. The effect is 49.4%, while other variables influence 50.6%. Recommendations are given to future researchers in Communication Studies to analyze vlogs further, starting from entertainment and educational vlogs to other interesting vlogs.